2007
DOI: 10.1038/sj.hdy.6800993
|View full text |Cite
|
Sign up to set email alerts
|

Neutral versus adaptive genetic variation in parasite resistance: importance of major histocompatibility complex supertypes in a free-ranging primate

Abstract: Current discussions in evolutionary ecology and conservation genetics focus on the relative importance of using selective neutral markers or markers of coding genes to identify adaptive and evolutionary relevant processes. Genetic diversity might be particularly important in immune genes (e.g., in genes of the major histocompatibility complex, MHC), which are influencing pathogen and parasite resistance. We investigated the effects of neutral versus adaptive genetic variation in parasite resistance in a natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
187
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(198 citation statements)
references
References 99 publications
9
187
2
Order By: Relevance
“…At the individual host level, susceptibility to helminths can result from one of the two alleles or from a co-dominant effect of both, also depending on the parasite in question 13 . It is common in studies of MHC diversity to use only alleles/supertypes, rather than genotypes in statistical analyses 5,6,44 . However, owing to the lack of knowledge of the genetic mechanism, and because working with genotypes would create sparse networks, we used supertypes and validated our analyses with genotypes 13 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the individual host level, susceptibility to helminths can result from one of the two alleles or from a co-dominant effect of both, also depending on the parasite in question 13 . It is common in studies of MHC diversity to use only alleles/supertypes, rather than genotypes in statistical analyses 5,6,44 . However, owing to the lack of knowledge of the genetic mechanism, and because working with genotypes would create sparse networks, we used supertypes and validated our analyses with genotypes 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies have shown an association between helminthic infections and certain MHC alleles 5,7,35,36 , each individual in the data set (Supplementary Data 1) was genotyped using a portion of the MHC class II DRB exon-2 functional gene that recognizes extracellular parasites such as helminths, by two independent runs of 454 GS-FLX sequencing following the procedure detailed in ref. 18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Now, new evidence comes from the study of a small nocturnal lemur living under natural conditions in western Madagascar. In the paper on page 265, by examining neutral microsatellite diversity, MHC-DRB exon 2 polymorphism and parasite burden, Schwensow et al (2007) found that MHC-DRB genotype is important for resistance to nematode helminths. They conclude that MHC polymorphism is maintained through pathogen-driven frequency-dependent selection in wild fattailed dwarf lemurs (Cheirogaleus medius).…”
mentioning
confidence: 99%